Bittersweet Monday - Lee, Jaime (Actor); Christopher, Philipp; Covington, David; LoGiudice, Lauren; Just 2 Me Productions (Firm); Leomark Studios (Firm) ([United States] : Just 2 me productions, 2014)
When two longtime best friends say their goodbye before a big move, they find themselves holding onto more than just their friendship. Separately in committed marriages, the two experience an emotional shift, exacerbated by the circumstances that bring them together and alone again. Transitioning into adulthood is a long and arduous process. But people often feel they should have everything figured out by a certain age, which rarely happens, if at all. Every character in the story struggles with a sense of dissatisfaction or void they don't quite understand. In the context of young marriages and careers, an effort to fix apparent issues ends up complicating things further, prompting an unforeseen set of dilemmas and realizations. But perhaps these complications are necessary to push things forward. This story, in the end, is that of love between two people. But sometimes, love is only everlasting in its impact on a person's path in life. Finding moments of deep completion with another human being can be a powerful fuel to bring about enough courage to face the unknown.
Originally released as a motion picture in 2014
Jaime Lee, Philipp Christopher, David Covington, Lauren LoGiudice, John Jude Schultz.
Cinematographer, Moses Lee ; editor, Jaime Lee ; music, David Park & Jaime Lee.
In English; with optional English subtitles.
Winner of an Award, at the Harlem International Film Festival 2013 : Mira Nair Award for Rising Female Filmmaker (Jamie Lee)
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 26, 2018).
Keywords: Friendship -- Drama; Man-woman relationships -- Drama; Romance films; Feature films; Internet videos; Streaming video